Uji Aktivitas Antibakteri Ekstrak Dan Fraksi N-Heksan, Etil Asetat, Air Dari Kulit Buah Kakao (Theobroma Cacao L.) Terhadap Bakteri Propionibacterium acnes ATCC 11827 Secara Difusi - Wijayanti, Sovie Nofia; Pratama, Kharisma Jayak; Permatasari, Desy Ayu Irma (Peneliti.net, 2023)
The skin of the cocoa fruit (Theobroma cacao L.) is one plant that can be used as an antibacterial. The skin of cocoa fruit (Theobroma cacao L.) contains chemical flavonoids, triterpenoids, and tannins. The purpose of this study was to determine ethanol extract and n-hexane fraction, ethyl acetate fraction, water fraction from cocoa fruit peel (Theobroma cacao L.) has antibacterial inhibitory power against Propionibacterium acnes ATCC 11827 bacteria and to determine between ethanol extract and n-hexane fraction, ethyl acetate fraction and the most active water fraction from cocoa fruit peel (Theobroma cacao L .) in inhibiting the growth of Propionibacterium acnes ATCC 11827. Cocoa peel powder (Theobroma caco L.) is macerated using 96% ethanol, then fractionated using n-hexane, ethyl acetate, and water solvents. Extract, n-hexane fraction, ethyl acetate fraction and water fraction were tested for antibacterial activity using diffusion method with concentrations of 3.125%, 6.25%, 12.5%, 25% and 50% against Propionibacterium acnes ATCC 11827 bacteria. The results of research on anatibacterial activity by diffusion method showed that extract, n-hexane fraction, ethyl acetate fraction and cocoa peel water fraction (Theobroma cacao L.) have inhibitory power against Propionibacterium acnes ATCC 11827 bacteria with the formation of an inhibition zone. The ethyl acetate fraction has the most effective antibacterial activity with concentrations of 3.12%, 6.25%, 12.5%, 25% and 50% having diameters of 8.56 mm, 9.76 mm, 9.83 mm, 13.33 mm and 15.5 mm. Based on the results of the study, it can be concluded that the ethyl acetate fraction is the most active fraction.